2019
DOI: 10.1371/journal.pone.0215429
|View full text |Cite
|
Sign up to set email alerts
|

What we know about management and organisation of primary dental care in Brazil

Abstract: This cross-sectional study evaluated the management and organisation of primary dental care in Brazil. For this purpose, data from the National Program for Improving Access and Quality of Primary Care (PMAQ-AB) were used. Dentists from 18,114 Oral Health Teams (OHTs) answered a structured questionnaire in 2014. The data were analyzed descriptively and by cluster analysis. Half the Brazilian OHTs (51.0%) undertake planning and programming of activities. The majority of OHTs (66.4%) conducted monitoring and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
6
0
6
Order By: Relevance
“…Other studies have revealed lacunas in the work process of the teams [ 26 , 35 , 51 , 58 ], but our research identifies alarming data, i.e., the increase in the prevalence of PHC teams with “worse completeness” in Cycle II, representing an increase in the proportion of teams that do not perform any of the work processes indicators surveyed, is considered a serious barrier to potential access to oral health services.…”
Section: Discussionmentioning
confidence: 61%
“…Other studies have revealed lacunas in the work process of the teams [ 26 , 35 , 51 , 58 ], but our research identifies alarming data, i.e., the increase in the prevalence of PHC teams with “worse completeness” in Cycle II, representing an increase in the proportion of teams that do not perform any of the work processes indicators surveyed, is considered a serious barrier to potential access to oral health services.…”
Section: Discussionmentioning
confidence: 61%
“…The linkage of team certification of the financial transfer may have created a bias in the responses; encouraging well-performing teams may not cause their actions to alter and discourage poorly performing teams from engaging in pay-per-performance-based incentive programs. 30 Dentists at CEOs and in the PHC have a record of their diagnosed patients showing that they know their role and seek to organize the work processes and case management for follow-up of the patients in the care network, and the construction of agendas agreed upon between the levels of care is fundamental for the management and resolution of the service. 31,32 The Northern and northeastern regions still present low percentages of follow-up of the cases, with findings similar to those found by Casotti et al, 33 the time elapsed between the suspicion and diagnosis should be as soon as possible; thus, it is essential to organize the network and attend to the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Health management should focus on appropriate interventions for individuals within a given population to diminish healthcare risks and costs 32 . In SUS, planning is a highly relevant aspect of health management 33,34 . In Spain and other countries with universal health care, it was also identified that management support could be a facilitator of interprofessional collaboration at PHC 27,29 .…”
Section: Discussionmentioning
confidence: 99%
“…32 In SUS, planning is a highly relevant aspect of health management. 33,34 In Spain and other countries with universal health care, it was also identified that management support could be a facilitator of interprofessional collaboration at PHC. 27,29 In the same sense, healthcare evaluation and monitoring also impacted the MSS.…”
Section: Discussionmentioning
confidence: 99%